Analisis Efisiensi Pengelolaan Pajak Restoran di Kantor Badan Pengelola Pajak dan Retribusi Daerah Kota Medan - Nabila Rizki Erjani; Muhammad Ihksan Harahap (Pusat Riset dan Inovasi Nasional, 2023)
Tax is an instrument for state revenue. Taxes are a tool for the government to achieve its goals of financing routine expenditure as well as national and community economic development. According to Law No. 28 of 2007 concerning General Provisions and Procedures for Taxation, Tax is the people's contribution to the state treasury which does not receive direct compensation and is used for State needs for the greatest prosperity of the people. This research aims to analyze the efficiency of restaurant tax management at the Medan City BPPRD Office. By using an analytical approach and describing the Medan City BPPRD restaurant tax management process, by providing an in-depth understanding of restaurant taxation practices. The results are expected to provide in-depth insight into the level of restaurant compliance with tax regulations, the effectiveness of the tax system, as well as recommendations for increasing efficiency in managing restaurant taxes in the Medan area.